M35 Relative lung and systemic bioavailability and oropharyngeal deposition of salbutamol inhaled through pMDI alone and with an improved able spacer. (December 2018) - Ammari, WG; Tayyem, R; Abu Fara, M; Sanders, M
Abstract : Introduction: Many patients using pressurised metered dose inhalers (pMDIs) have difficulties coordinating the beginning of inhalation with device actuation which adversely affects lung deposition. Valved holding chambers (known as spacers) are attached to pMDIs to overcome this problem. A recently improved version of Able spacer (AS) (Clement Clarke International, UK) is made of a special transparent polymer that incorporates silver ion anti-microbial technology to protect from contamination and microbial growth. The AS valve has been improved to operate at low flows typical of tidal flow rates of younger patients. Our study aimed to evaluate the relative lung and systemic bioavailability and oropharyngeal deposition of salbutamol following inhalation through Ventolin pMDI alone and with AS. Methods: Ethical approval was obtained to enrol healthy, adult volunteers into an investigational, two-period, randomized, crossover study. In each period, subjects were trained rigorously to inhale 2 doses, separated by 30–60 s, of 100 µg salbutamol per dose from the pMDI either alone or attached to AS. Immediately after each dose inhalation, the subject was given 20 mL water to mouthwash and gargle, which was then pooled for salbutamol assay. Each volunteer gave urine samples 0.5 hour (pre-) and 0.5 hour post-inhalation. Then, they pooled their urine over 24 hours post-inhalation. The volume and pH of the urine were recorded. A one week washout separated the study periods. The relative lung bioavailability (by 30 min urinary salbutamol excretion pharmacokinetic method – USAL0.5), systemic bioavailability (0.5–24 hour urinary excretion of salbutamol and its metabolite – USALMET24) and oropharyngeal deposition were evaluated. Salbutamol levels were quantified using in-house developed solid phase extraction and LC-MS/MS methods. Results: Ten male subjects (Mean (SD) age: 30.7 (9.9) years) participated. The study results are presented in table 1. Statistically, the AS increased significantly (p<0.05) the salbutamol delivery to the lungs and reduced (p<0.001) its oropharyngeal impaction, compared with pMDI alone. Both inhalation methods gave comparable systemic salbutamol exposure (p>0.05). Conclusion: The Able spacer improves the inhaled salbutamol dose to the lungs and minimizes its precipitation in the oral cavity. This can give an added therapeutic benefit particularly in subjects with pMDI technique issues.